FUZZY MULTIPLE ATTRIBUTE DECISION MAKING IN HOTEL SELECTION - Aprilia, Rima (UIN Sumatera Utara Medan, 2018)
As the third largest city in Indonesia, Medan has become one of the cities visited by many tourists, so many hotels have sprung up, from just guest houses to star hotels with various facilities provided. In the selection of hotels to stay, Fuzzy Multiple Attribute Decision Making is expected to provide the best solution in these problems. So that when tourists come to Medan, they can choose the best hotel that suits their needs. The output of this study, the collection of relevant references to the formulation of the problem. The aim is to strengthen the problem and as a theoretical basis for conducting the study and also become the basis for designing decision support systems